Ongoing Supplementation of Probiotics to Cesarean-Born Neonates during the First Month of Life may Impact the Gut Microbial - Yang, Wenqing; Tian, Liang; Luo, Jiao; Yu, Jialin (American Journal of Perinatology, 2020)
Objective The delivery mode is considered to be a significant influencing factor in the early gut microbiota composition, which is associated with the long-term health of the host. In this study, we tried to explore the effects of probiotics on the intestinal microbiota of C-section neonates.Study Design Twenty-six Chinese neonates were enrolled in this study. The neonates were divided into four groups: VD (natural delivery neonates, n = 3), CD (cesarean-born neonates, n = 9), CDL (cesarean-born neonates supplemented with probiotic at a lower dosage, n = 7), and CDH (cesarean-born neonates supplemented with probiotic at a higher dosage, n = 7). Fecal samples were collected on the 3rd, 7th, and 28th day since birth. The V3–V4 region of the 16S ribosomal ribonucleic acid gene was sequenced by next-generation sequencing technology.Results The α-diversity of the intestinal microbiota of cesarean delivery neonates was significantly lower than that of the naturally delivered neonates on the 28th day (p = 0.005). After supplementation with probiotics for 28 days, the α-diversity and the β-diversity of the gut flora in the cesarean-born infants (CDL28 and CDH28) was similar to that in the vaginally delivery infants. Meanwhile, the abundances of Lactobacillus and Bifidobacterium were significantly increased since the 3rd day of probiotic supplementation. Besides, the sustained supplementation of probiotics to neonates would help improve the abundance of the operational taxonomic units in several different Clusters of Orthologous Groups of proteins.Conclusion This study showed that probiotics supplementation to cesarean-born neonates since birth might impact the diversity and function of gut microbiota.Key Points
Keywords: neonates; cesarean; probiotics; intestinal microbiota; 16S rRNA